Analysis of energy efficiency in South Africa's primary mineral industry: a focus on gold - Johnston, Oliver Ross (Energy Research Centre, 2016)
Energy use is the human activity responsible for the majority of its greenhouse gas emissions. In 2010 the global energy-related emissions of carbon dioxide - the principal greenhouse gas-jumped by 5.3% from the previous year, to a record 30.4 gigatonnes (IEA 2011a). The International Energy Agency (2011) has projected that the world's primary energy demand could increase by 33% and that energy related CO2 emissions will increase by 20% to 36.4 Gt between 2010 and 2035 (IEA 2011a). South Africa is one of the most energy intensive countries in the world, measured as GHG emissions per Gross Domestic Product produced. South Africa's energy intensiveness is a result of the energy intensive nature of a number of its key industries. The mineral industry is one such industry. It plays a crucial role in South Africa's economy and is the largest industry in its primary economic sector (Chamber of Mines 2010). Energy efficiency has been identified as one of the cheapest and most effective measures to reduce energy consumption and its associated greenhouse gas emissions. The Long Term Mitigation Scenarios coordinated by the University of Cape Town's Energy Research Centre identified that South Africa's industrial sector had cumulatively the greatest potential to reduce its GHG emissions through improved energy efficiency, ahead of the commercial, residential or transport sectors(Winkler 2007). South Africa's continued reliance on unsustainable energy production, particularly coal, increases the need for maximising energy efficiency to mitigate resource consumption and the GHG emissions associated with the production and use of fossil fuel generated energy. This project aims to identify and holistically evaluate the potential opportunities that exist for the reduction of energy and climate footprints of South Africa's gold industry sub-sector, with the aim of providing guidance to both government and industry for a path towards a more energy efficient industry with lower associated GHG emissions. To this end the thesis begins with a comprehensive review of the potential drivers, barriers and opportunities for increased EE and GHG emissions mitigation for the local minerals industry.